Respuesta :

Answer:

2 1/2

Step-by-step explanation:

X^1 - x^-1 + x^0

Let x=2

2^1 - 2^(-1) +2^0

We know that negative exponents put the number in the denominator  and anything to the zero power is 1

2 - 1/2 +1

Rewriting

2+1-1/2

3-1/2

2 1/2

Answer:

For x = 2 the value of the expression is 2.5

Step-by-step explanation:

the given expression is [tex]x^{1} - x^{-1} + x^{0} = x -(\frac{1}{x}) + 1[/tex]

Simplifying further [tex]\frac{x^{2}-1 }{x} + 1[/tex]

Now if we put the value of x = 2 in the simplified form of the expression we get

[tex]\frac{x^{2} - 1}{2} + 1[/tex] = [tex]\frac{4-1}{2} + 1 = \frac{3}{2} + 1 = 1.5 + 1 = 2.5[/tex]